A novel approach to transform an open circuit series stub to a short circuit shunt stub for the implementation of high‐pass butterworth filter. Issue 3 (28th January 2013) - Shoaib, Nosherwan; Shoaib, Imran; Shoaib, Sultan
Abstract A new approach for transforming an open circuit series stub to short circuit shunt stub is presented.A mathematical identity is also derived. Additional transmission lines of particular lengths are also used while performing this transformation. The simulations and the experimental results verified that the derived mathematical identity can be used for the implementation of high‐pass maximum flat Butterworth filter. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:497–501, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27354